Characteristics of Lightweight Concrete for Sustainable Housing Development - Fahrizal Zulkarnain Jurnal Dosen; Mahyuddin Ramli Jurnal Dosen (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2016)
Lightweight concrete is a concrete which by one means or another has been made lighter than conventional concrete, the very familiar product made from sand and gravel or crushed rock and cement, which has for so long been an important all-round building material. The most obvious characteristic of lightweight concrete is of course its density, which is always considerably less than and often only a fracion of that of ordinary concrete. The are many advantages in low density, such as reduction of dead load, faster building rates, and lower haulage and handling costs. The density of structural lightweight aggregate concretes can range from approximately 1200 to 2000 kg/m3 compared with 2300 to 2500 kg/m3 for normal weight concrete. The use of lightweight concrete has sometimes made it possible to proceed with a design which otherwise would have been abandoned, because of exercise weight. In framed structures, considerable savings in cost can be brought about by using lightweight concrete floor, partitions, and external cladding.